Ocean Wave Modelling in Cempi Bay, West Nusa Tenggara during Northwest and Southeast Monsoon - Hidayat, Esa Fajar; Havis, Muchammad Iqbal; Sembiring, Agustinus; Fahlevy, Karizma; Abdullah, Faizal Ade Rahmahuddin (University of Diponegoro, 2025)
Coastal regions in Indonesia, such as Cempi Bay in West Nusa Tenggara, are strongly influenced by seasonal monsoon systems, which significantly affect wave dynamics and coastal processes. As the Northwest Monsoon (NWM) and Southeast Monsoon (SEM) exert non-uniform effects along Indonesia’s coastline, accurate wave modeling is essential to support coastal management, fisheries, and disaster mitigation in this area. This study applies a numerical wave model driven by monsoonal wind data, supplemented with bathymetry and open-boundary conditions, to simulate and analyze ocean wave characteristics in Cempi Bay during the NWM and SEM periods, focusing on significant wave height ( ) and dominant wave period ( ). Model performance was evaluated using Mean Absolute Percentage Error (MAPE), correlation coefficient ( ), and Root Mean Square Error (RMSE). During NWM, achieved a MAPE of 15.49%, = 0.55, and RMSE = 0.19 m, indicating good agreement, while the initial SEM run showed a high MAPE of 42.83% for that improved to 20.16% after scaling the input by 79%, reducing the RMSE from 0.48 m to 0.26 m and increasing from 0.67 to 0.68. Spatial analysis revealed distinct wave propagation patterns between the monsoons and confirmed lower wave energy in the inner part of Cempi Bay, highlighting the importance of capturing seasonal wave variability for effective coastal infrastructure planning and monsoon-adapted management strategies.